DAMPAK PEMBANGUNAN PERUMAHAN KAWASAN PINGGIRAN KOTA TERHADAP MASYARAKAT SETEMPAT, STUDI KASUS KECAMATAN GEDEBAGE, BANDUNG (Impact of Housing Development of Zone Suburbs Against the Local Community, Case Study: District Gedebage, Bandung) - Arief Rahman (Tesa Arsitektur, 2015)
The development of suburban areas occur because people are attracted by the new place of residence or employment, but socio-economically they are still oriented to the core city. Other phenomena of suburban developments, namely the restructuring of the core city functions as a result of the shift from a manufacturing center to a center of financial activities (finance), and services, while manufacturing activity has increasingly shifted to the edge of the area. The purpose of this study was to determine the socio-economic impacts of housing development outskirts of Bandung, District Gedebage on local communities. The research method used was a quantitative approach and equipped with qualitative data. The case study is a reseach that analyze one case conducted intensive, in-depth, detailed, and comprehensively. This study is a beginning, there is expected to further research with more samples so that the data is valid